L'homme de la cave = The man in the basement [videorecording (DVD)] - Toussaint, Anne-Dominique; Le Guay, Philippe, 1956-; Taurand, Gilles; Weitzmann, Marc; Cluzet, François; Renier, Jérémie; Bejo, Bérénice, 1976- (Kino Lorber, 2023)
After a Jewish couple sells their basement to a former history teacher, they discover his secret life as an anti-Semitic conspiracy theorist. As the couple struggles to rescind the sale, the buyer befriends their naive teenage daughter.